Measurement of b hadron lifetimes in pp collisions at root s=8TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
Measurements are presented of the lifetimes of the B0, B0 s, 0 b, and B+ c hadrons using the decay channels B0 → J/ψK∗(892)0, B0 → J/ψK0 S, B0 s → J/ψπ+π−, B0 s → J/ψφ(1020), Λ0 b → J/ψ0, and B+ c → J/ψπ+. The data sample, corresponding to an integrated luminosity of 19.7 fb−1, was collected by the CMS detector at the LHC in proton–proton collisions at √s = 8 TeV. The B0 lifetime is measured to be 453.0 ± 1.6 (stat) ± 1.8 (syst)µm in J/ψK∗(892)0and 457.8 ± 2.7 (stat) ± 2.8 (syst)µm in J/ψK0 S, which results in a combined measurement of cτB0 = 454.1 ± 1.4 (stat) ± 1.7 (syst)µm. The effective lifetime of the B0 s meson is measured in two decay modes, with contributions from different amounts of the heavy and light eigenstates. This results in two different measured lifetimes: cτB0 s→J/ψπ+π− = 502.7 ± 10.2 (stat) ± 3.4 (syst)µm and cτB0 s→J/ψφ(1020) = 443.9 ± 2.0 (stat) ± 1.5 (syst)µm. The 0 b lifetime is found to be 442.9 ± 8.2 (stat) ± 2.8 (syst)µm. The precision from each of these channels is as good as or better than previous measurements. The B+ c lifetime, measured with respect to the B+ to reduce the systematic uncertainty, is 162.3 ± 7.8 (stat) ± 4.2 (syst) ± 0.1 (τB+ )µm. All results are in agreement with current world-average values.